CRITICALLY READING FIGURATIVE LANGUAGE IN NEWS TITLE OF IDN TIMES.COM: WORLD CUP CHANNEL - Andini Firdariani; Zubaedah Wiji Lestari; Tendy Somantri (Universitas Wiralodra, 2024)
Figurative language is a style of language that is used to beautify a sentence. Not only in poetry and songs, figurative language is also often used in news titles. The research aims to critically read the figurative language found in IDN Times.com news titles, especially the types and functions of the figurative language contained in the news titles of IDN Times.com. The research critically read types of figurative language and critically read functions of figurative languages found in news titles of IDN Times.com World Cup Channel in December 2022 Edition. To collect the data, researchers used the descriptive qualitative method by doing several ways such as: reading news titles, classifying news titles based on the figurative language type, and writing down the news titles. The finding shows that there are four types of figurative language in IDN Times.com, including twenty-five Metaphors, three personifications, one simile, and ten hyperboles. The functions of using figurative language in the news title are to compare something with something that has a similar meaning, making the inanimate like a human, and to dramatize a sentence. Generally, figurative language makes every sentence appear more lovely and meaningful.